A relação entre a tecnologia da informação e comunicação e a competitividade: estudo em empresas do pólo calçadista de Jaú/SP - Zem-lopes, Aparecida Maria (2009)
Jaú´s region, in the center of the State of São Paulo, is home for a group of companies specialized in the production of women shoes. They are industries, studios or backstitch stands, raw material suppliers, machines and equipments, for the whole productive chain of the shoes industries, including the tanneries, responsible for the supply of the main raw material used: the leather. This structure allows the denomination of this area as Local Cluster, where several players, from public and private sectors, articulate themselves together seeking increase in productivity and competitiveness in the market sector. To best use these arrangements and to increase their efficiency of their actions, it is necessary the use of information and communication technologies that can optimize their processes and information flows, improving their competitiveness. In this context, this exploratory and descriptive research aimed to identify the paper of the Information and Communication Technology and its influence on the competitiveness of these companies based on some indicators like design, quality of the products, flexibility of the production, human resources, infrastructure and others. The collection of data was accomplished through interviews with the managers of a sample of these companies, using the interview instrument elaborated this research, following the appropriate ethical precepts. The results of the interviews indicated a disagreement on forms of management by the accounted companies, which leads to only 10% of them taking part on the Local Cluster. The remaining ones not only do not participate in the cluster, but also show no interest in getting involved in larger events, such as local, regional or national trade fairs, important for the competitiveness of these companies. It is critical for the survival and growth of the cluster a larger awareness of the importance of the junction of efforts by the companies, through a greater fulfillment of meetings, so that they may share problems and solutions and start seeing each other as partners, not rivals. The results obtained will be disseminated to companies and players in the region with a view to supporting the development of the Local Cluster.